2000
DOI: 10.1258/1357633001935374
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of satisfaction with telemedicine among health-care professionals

Abstract: A survey was conducted among non-doctor health-care professionals in six rural counties in Missouri. The purpose of the survey was to establish baseline data to evaluate the effect of changes in the health-care sector, especially technology changes, on the job satisfaction, career satisfaction, relationships and communication activities of health professionals. The survey included three rural counties in which integrated telecommunication and interactive video telemedicine services were being installed, but be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…5 A number of studies attest to the feasibility and acceptability of telemedicine-linked MDT meetings in oncology [6][7][8][9] for a variety of cancers, including breast, 10 head and neck, 11 gynaecological, 12,13 lung 10,14 and colorectal cancer. 10 Health professionals are generally supportive of telemedicine [15][16][17] and of tele-oncology. 7,13 However, there is no internationally agreed, comprehensive methodology for evaluating the clinical, technical and economic effectiveness of telemedicine in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…5 A number of studies attest to the feasibility and acceptability of telemedicine-linked MDT meetings in oncology [6][7][8][9] for a variety of cancers, including breast, 10 head and neck, 11 gynaecological, 12,13 lung 10,14 and colorectal cancer. 10 Health professionals are generally supportive of telemedicine [15][16][17] and of tele-oncology. 7,13 However, there is no internationally agreed, comprehensive methodology for evaluating the clinical, technical and economic effectiveness of telemedicine in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a high degree of satisfaction among patients who received their health-care by means of telemedicine [1][2][3][4][5][6] . Health professionals also have a favourable attitude towards telemedicine [7][8][9] . Telemedicine in oncology, tele-oncology, is a good example of how this technique can improve communication up and down the health-care pyramid (tertiary, secondary and primary care) [10][11][12] .…”
mentioning
confidence: 99%
“…27 Hicks et al found that approxiamtely onethird of the surveyed health professionals agreed that technological applications in the healthcare system have a large effect on their work. 28 In the current study, 193 (36.9%) participants believed that telenursing could enhance staff efficacy in the health system and 386 (73.8%) participants believed that telenursing could reduce nursing care costs. Glinkowski et al also indicated that telenursing could decrease healthcare expenditures, facilitate contact with patients and enhance medical staff productivity.…”
Section: Discussionmentioning
confidence: 66%